Digital competences and skills as key factors between connectedness and tolerance to diversity on social networking sites: Case study of social work graduates on Facebook. - Castillo-de-Mesa, Joaquín; Gómez-Jacinto, Luís (Sage, 2021)
Social networking services are becoming parallel socialization universes. In these digital contexts, people tend to connect with others who share their perspectives and opinions about the world. Emerging voices are warning about the growing homophily resulting from these forms of socialization, which can have a negative impact on tolerance to diversity and the quality of social capital. Relational approach disciplines such as social work can provide digital skills and competences to improve the manner in which these services are used. In this article, the authors analyse how patterns of connectedness among social work graduates affect tolerance to diversity and social capital. A sample of 126 social work graduates was analysed to assess their connectedness patterns on Facebook. Participants were also asked about their digital competences and skills in order to know how these variables can mediate the achievement of tolerance to diversity and social capital. Results show that higher connectedness, when social work graduates have digital skills on Facebook, leads to higher tolerance to diversity and social capital. In order to counteract homophily, social workers must encourage users to acquire digital skills thus increasing tolerance for diversity.
https://openpolicyfinder.jisc.ac.uk/publication/9106?from=single_hit
Keywords: Redes sociales en Internet; Conducta informacional; Connectedness; Digital competences; Digital skills on Facebook; Social capital; Tolerance to diversity